2022
DOI: 10.7759/cureus.29331
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Consequences Associated With Coronary Artery Bypass Graft Surgery: A Bibliometric Analysis

Abstract: The current paper explores the mutual impact of psychological factors and cardiac surgery on each other using bibliometric analysis with the help of indicative cited publications, co-cited journals, and collaborations between countries, institutions, and authors. Citation analysis is an attractive methodology because it provides quantitative information that is readily acquired with electronic databases and that can be compared across topic areas. The bibliometric investigation was done using the PubMed databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, Farkas et al (2023) found that aerobics can reduce anxiety levels and improve emotional states [ 13 ]. Similarly, Jain et al (2022) showed that aerobics training could help reduce depressive symptoms and improve quality of life [ 14 ]. These findings highlighted the potential of aerobics as a form of mental health promotion.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Farkas et al (2023) found that aerobics can reduce anxiety levels and improve emotional states [ 13 ]. Similarly, Jain et al (2022) showed that aerobics training could help reduce depressive symptoms and improve quality of life [ 14 ]. These findings highlighted the potential of aerobics as a form of mental health promotion.…”
Section: Methodsmentioning
confidence: 99%